Abnormal expression of the human CD44 gene in early colorectal malignancy with special reference to variant exon 9 (9v). Issue 6 (June 1996) - Kawahara, K; Yoshino, T; Kawasaki, N; Miyake, K; Akagi, T
Abstract : AIMS: To examine the expression of CD44 variant exon 9 in early colorectal malignancies. METHODS: Formalin fixed, paraffin wax embedded tissue sections from 30 cases of tubular adenoma and 35 cases of adenoma with focal carcinoma of the colon were examined immunohistochemically using a monoclonal antibody (MAb 11.24) directed against CD44-9v. RESULTS: In the normal colorectal mucosa immunoreactivity was confined to the basal part of the crypts and was expressed in less than 10% of crypt cells. CD44-9v was expressed in the superficial part of tubular adenoma with mild atypia in 67% of the cases and in 19% of the tumour cells. The immunoreactivity was observed along the basement membrane in mild atypia, as in the non-neoplastic crypts. In the course of progression to severe atypia the spatial polarity of immunoreactivity was lost, and the extent of CD44-9v expression increased in intensity and in the percentage of positive cases and positive cells. In the carcinomatous lesions of adenoma with focal carcinoma, 94% of the cases and 44% of the tumour cells were positive for CD44-9v protein. CONCLUSION: CD44-9v may be overexpressed at the early stage of colorectal tumorigenesis and this increase continues throughout the course of the disease.